Factors Affecting Teachers Attitude towards Implementing E-Learning in Jordan - Al-Zoubi, Qusai Mohammad Ibrahim; Annamalai, Subashini; Ab Salam, Sobihatun Nur (2018)
This study examines to find out the factors that affect the attitude of teachers in the implementation of E-Learning in Jordanian secondary schools and also to find out the level of deployment of E-Learning facilities and resources in Jordanian secondary schools. As a preliminary study, literature was reviewed and the finding showed that even though several attempts were made to the deployment of E-Learning into the Jordanian secondary schools, it has met resistance from the teachers whose attitude were hindering the success of implementing E-Learning in Jordanian schools. Among the factors responsible for the teachers’ attitude was lack of competence with use of the E-Learning platform which in turn stabbed their confidence in using the E-Learning and also cultural influences as Muslim women are not allowed to have a one on one interaction with the male lecturers as modesty is enjoyed upon each other by Muslims. The capital expenditure by the Jordanian Government in incorporating Information and Communication Technology (ICT) in secondary school education has not started to yield positive results.